CASE STUDY ON EBSTEIN’S ANOMALY AND THE VALUE OF CARDIAC MRI IN PREOPERATIVE DIAGNOSIS - Lương, Quang Huy; Nguyễn , Thị Huyền; Nguyễn , Ngọc Tráng; Vũ , Đăng Lưu (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Ebstein’s anomaly (EA) is a rare congenital heart disease characterized by downward displacement of the septal and inferior tricuspid valve leaflets, redundant anterior leaflets with a sail-like morphology, and atrialization of the inlet portion of the right ventricle. The clinical manifestations of EA are not specific and range from asymptomatic to severe as dictated by the degree of tricuspid valve displacement, the severity of tricuspid regurgitation, effective right ventricular volume, and the presence of associated malformations such as an atrial septal defect, arrhythmias. We report a case of a 42-year-old female patient with a history of EA diagnosed many years ago, with irregular treatment. Three months prior to admission, the patient began experiencing progressively worsening shortness of breath, leading to hospitalization at Bach Mai Hospital, where she was stabilized with medication and assessed for surgery. The echocardiogram report showed changes in the description of the morphology and attachment sites of the valve leaflets across different examinations. The patient underwent a pre-surgical cardiac magnetic resonance imaging (CMR). She was then surgically treated with the Cone technique for tricuspid valve repair. After surgery, her condition significantly improved.